1997
DOI: 10.1016/s0092-8674(00)80334-7
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of BMP7 and SHH in the Induction of Forebrain Ventral Midline Cells by Prechordal Mesoderm

Abstract: Ventral midline cells at different rostrocaudal levels of the central nervous system exhibit distinct properties but share the ability to pattern the dorsoventral axis of the neural tube. We show here that ventral midline cells acquire distinct identities in response to the different signaling activities of underlying mesoderm. Signals from prechordal mesoderm control the differentiation of rostral diencephalic ventral midline cells, whereas notochord induces floor plate cells caudally. Sonic hedgehog (SHH) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
196
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(207 citation statements)
references
References 47 publications
10
196
0
Order By: Relevance
“…Injection of E13.5 mouse embryos with an hybridoma producing a Shh-blocking antibody (and analyzed at E18.5) alters the distribution of RGC axons at the optic chiasm with an enlargement of the overall region occupied by RGC fibers at the midline and axon extension in aberrant directions. However, as Shh activity is important to pattern the midbrain regions surrounding the ventral hypothalamus (just adjacent to the optic chiasm) during retinal axon development (Dale et al, 1997;Barresi et al, 2005;Manning et al, 2006), it is likely that blocking Shh signaling for 5 d in developing embryos can cause patterning defects. Thus, as noted by the authors (Sánchez-Camacho and Bovolenta, 2008), it is possible that the effects observed are not due to a direct guidance effect of Shh but rather to changes in expression of other guidance cues.…”
Section: The Roles Of Shh In the Guidance Of Rgc Axonsmentioning
confidence: 99%
“…Injection of E13.5 mouse embryos with an hybridoma producing a Shh-blocking antibody (and analyzed at E18.5) alters the distribution of RGC axons at the optic chiasm with an enlargement of the overall region occupied by RGC fibers at the midline and axon extension in aberrant directions. However, as Shh activity is important to pattern the midbrain regions surrounding the ventral hypothalamus (just adjacent to the optic chiasm) during retinal axon development (Dale et al, 1997;Barresi et al, 2005;Manning et al, 2006), it is likely that blocking Shh signaling for 5 d in developing embryos can cause patterning defects. Thus, as noted by the authors (Sánchez-Camacho and Bovolenta, 2008), it is possible that the effects observed are not due to a direct guidance effect of Shh but rather to changes in expression of other guidance cues.…”
Section: The Roles Of Shh In the Guidance Of Rgc Axonsmentioning
confidence: 99%
“…Perhaps not surprisingly given their key regulatory actions, misregulation of Hh signaling has been shown to contribute to various pathologies, most notably various cancers including basal cell carci- Bellusci et al 1997;Littingtung et al 1998;Pepicelli et al 1998 Muscle Shh Induction/proliferation/survival epaxial muscle precursors, fiber-type identity, regulation smooth muscle differentiation Johnhson et al 1994;Munsterberg et al 1995;Blagden et al 1997;Duprez et al 1998;Pepicelli et al 1998;Borycki et al 1999;Duprez et al 1999;Lewis et al 1999;Norris et al 2000;Sukegawa et al 2000;Coutelle et al 2001;Kruger et al 2001 Echidna, twhh Muscle/fiber-type identity Currie and Ingham 1996;Du et al 1996 Neural Crest Shh Survival cranial neural crest, cranial facial morphogenesis, proliferation/ differentiation sympathetic cells Helms et al 1997;Ahlgren and Bronner-Fraser 1999;and Williams et al 2000;Garg et al 2001 Neurons Shh Induction of specific ventral neural cell types, proliferation/survival/death neural precursors Echelard et al 1993;Kraus et al 1993;Roelink et al 1994;Ericson et al 1995;Hynes et al 1995;Marti et al 1995;Roelink et al 1995;Wang et al 1995;Belloni et al 1996;Chiang et al 1996;Ericson et al 1997;Dale et al 1997;Kohtz et al 1998;Ye et al 1998;Briscoe et al 1999;…”
mentioning
confidence: 99%
“…Shh binding to Patched is thought to relieve Patched-mediated inhibition of Smoothened activity, resulting in the activation of transcriptional targets by members of the Gli family (Ingham et al, 1991;for review, see Ingham, 1998). Although Patched and Gli-1 appear to be general transcriptional targets in vertebrates, other factors are specific to neural precursor cells, including HNF3␤ and Nkx-2.2 (Dale et al, 1997;Ericson et al, 1997).…”
mentioning
confidence: 99%